Pre-Toddler Development Examination Screening (KPSP) at Posyandu Jatikalang Village, Prambon District, Sidoarjo Regency: Skrining Pra Pemeriksaan Perkembangan Balita (KPSP) Di Posyandu Desa Jatikalang Kecamatan Prambon Kabupaten Sidoarjo - Mudlikah, Siti; Putri, Lidia Aditama (Universitas Muhammadiyah Sidoarjo, 2021)
Delay in the development of children under five occurs around 10% in children aged <5 years. The purpose of community service activities is to carry out checks on child development and assess child development using the Pre-Screening Questionnaire for Child Development. The method uses interviews and observations. The study population is all mothers who have children under five, the sample is all children aged <5 years who come to the posyandu. The results show that the age period of children 3 - 72 months, the majority of children aged 15 months are 11 children (14%), 6 months of age are 10 children (12.9%), 30 months of age are 9 children (11.6%), age 3 month totaling 8 children (10.3%). While children with appropriate development are 65 children (83%), development children are doubting 12 children (15.4%) and children with deviant development are 1 child (1.3%). Thus children who have doubts and deviant developments need to do counseling and stimulation interventions to improve children's optimal developmental abilities.